HIV care continuum outcomes among recently diagnosed people with HIV (PWH) in Washington, DC. (30th January 2023) - Jaurretche, Maria; Byrne, Morgan; Happ, Lindsey Powers; Levy, Matt; Horberg, Michael; Greenberg, Alan; Castel, Amanda D.; Monroe, Anne K.
Abstract: The Ending the HIV Epidemic initiative aims to decrease new HIV infections and promote test-and-treat strategies. Our aims were to establish a baseline of HIV outcomes among newly diagnosed PWH in Washington, DC (DC), a 'hotspot' for the HIV epidemic. We also examined sociodemographic and clinical factors associated with retention in care (RIC), antiretroviral therapy (ART) initiation and viral suppression ( VS ) among newly diagnosed PWH in the DC Cohort from 2011–2016. Among 455 newly diagnosed participants, 92% were RIC at 12 months, ART was initiated in 65% at 3 months and 91% at 12 months, VS in at least 17% at 3 months and 82% at 12 months and 55% of those with VS at 12 months had sustained VS for an additional 12 months. AIDS diagnosis was associated with RIC (aOR 2.99; 1.13–2.28), ART initiation by 3 months (aOR 2.58; 1.61–4.12) and VS by 12 months (aOR4.87; 1.69–14.03). This analysis contributes to our understanding of the HIV treatment dynamics of persons with recently diagnosed HIV infection in a city with a severe HIV epidemic.